1994
DOI: 10.1111/j.1753-6405.1994.tb00231.x
|View full text |Cite
|
Sign up to set email alerts
|

What causes basal cell carcinoma to be the commonest cancer?

Abstract: We conducted a hospital‐based case‐control study in Brisbane, Queensland, to investigate the specific determinants of basal cell carcinoma (BCC), as distinct from squamous cell carcinoma (SCC), with emphasis on ancestry, residential history, pigmentary characteristics, sun sensitivity and other constitutional factors. The sample was recruited from a dermatology outpatient clinic during an eight‐week period in 1991, and comprised 51 incident or recently diagnosed cases of BCC, and 112 randomly selected controls… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
22
0
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 66 publications
(30 citation statements)
references
References 11 publications
4
22
0
3
Order By: Relevance
“…Previous studies have reported a higher incidence of BCCs in men relative to women across the body as a whole 1 14. Our data focused specifically on periocular BCCs (eyelid including the canthi) and we found partial concordance with these previous studies.…”
Section: Discussionsupporting
confidence: 89%
See 1 more Smart Citation
“…Previous studies have reported a higher incidence of BCCs in men relative to women across the body as a whole 1 14. Our data focused specifically on periocular BCCs (eyelid including the canthi) and we found partial concordance with these previous studies.…”
Section: Discussionsupporting
confidence: 89%
“…This is in keeping with previous reports of BCCs more broadly across the body as a whole 13. It has been postulated that this is in part due to cumulative damage from ultraviolet radiation (sun damage) with resultant DNA damage along with a potential reduction in DNA repair mechanisms 14. With increasing life expectancy and increased duration of exposure to risk factors, the overall burden of BCC is not likely to diminish.…”
Section: Discussionsupporting
confidence: 85%
“…The relationship between overweight and a decreased BCC risk has already been reported by others (Gilbody et al , 1994; van Dam et al , 1999; Gerstenblith et al , 2012; Pothiawala et al , 2012). It has been proposed that obese individuals engage less in physical activity, therefore spend less time outdoors, and wear less revealing clothing, which leads to reduced sun exposure of the skin.…”
Section: Discussionsupporting
confidence: 74%
“…Overall, BCC is the most common malignant eyelid tumor in the world [1, 40], with a male predilection [41]. However, it has been reported that eyelid BCC is more common in young females (< 50 years) [39].…”
Section: Discussionmentioning
confidence: 99%